Evaluation of the environmental performance of rice husk ash and tire rubber residues incorporated in concrete slabs. (28th November 2022) - Sampaio, Daniel O.A.; Tashima, Mauro M.; Costa, Daniele; Quinteiro, Paula; Dias, Ana Cláudia; Akasaki, Jorge L.
Highlights: Assessment of sand and tire rubber residue and cement and rice hulk ash trade-offs. Concrete slabs without wastes incorporated had higher environmental impacts. The slab with more rice husk ash ranked as the best environmental option. Raw materials production represented most of the total environmental impacts. Wastes transport distances had a low influence on the results. Abstract: This study analyses the potential environmental impacts of the use of tire rubber residue (TRR) and rice husk ash (RHA) for the production of concrete slabs in Brazil, to support decision-making regarding management alternatives for TRR and RHA. Three scenarios were assessed: (1) slab production without inclusion of TRR or RHA (discarded in landfills); (2) slab production with incorporation of TRR alone; and (3) slab production with incorporation of TRR and RHA. The impact assessment based on the ReCiPe 2016 method showed that Scenario 3 had the lowest environmental impacts and Scenario 1 had the highest impacts.